Totally aromatic liquid crystal polymer composition
Patent Information
- Application Number
- JP2025058415
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026165818000001 
Figure 2026165818000002 
Figure 2026165818000003
Abstract
Description
Technical Field
[0001] The present invention relates to a wholly aromatic liquid crystal polymer composition that excels in the balance of flame retardancy, thin-wall flowability, heat resistance and mechanical strength.
Background Art
[0002] Liquid crystal polymers have excellent moldability and high heat resistance, and by leveraging these properties, they are mainly used in applications of electronic components such as connectors, relays, and bobbins. In recent years, electronic components have been increasingly highly integrated, miniaturized, thinned and reduced in wall thickness, and the trend toward miniaturization and thinning of wall thickness is particularly notable among connector components.
[0003] Representative examples of such thinned-wall connectors include Board to Board connectors used to join printed wiring boards to each other, and connectors for flexible printed circuits (FPC) used to connect flexible printed boards to printed wiring boards.
[0004] Board to Board connectors and FPC connectors are required to have heat resistance to withstand reflow soldering, and in addition, the components themselves are required to be miniaturized along with the miniaturization of electronic devices using printed wiring boards. For example, narrow-pitch connectors with a pitch of 0.3 mm to 0.4 mm between the metal terminals of the connectors have been provided. In addition, low-profile connectors with a stacking height of 0.6 mm in the fitted state of the connector are also provided.
[0005] Along with the miniaturization and thinning of wall thickness of electronic components, the demand for materials that achieve both thin-wall flowability and flame retardancy is increasing. However, in general, even for the same resin material, thinning the wall makes it difficult to ensure flame retardancy, and in addition, materials with excellent thin-wall flowability are prone to resin dripping when exposed to flame, which as a result makes it difficult to ensure flame retardancy. Therefore, it has been technically difficult to achieve both excellent thin-wall flowability and high flame retardancy.
[0006] Methods have been proposed to improve the flame retardancy of liquid crystal polymers by adding halogen-based flame retardants (Patent Document 1), silicones (Patent Document 2), phosphorus-based compounds (Patent Document 3), and red phosphorus (Patent Document 4).
[0007] While adding these substances does improve flame retardancy to some extent, halogenated flame retardants are generally considered to have high persistence and bioaccumulation in the environment, and harmful substances are released during combustion or heating, raising concerns about their impact on human and biological health. Furthermore, adding red phosphorus cannot be used in applications where a white color is required, and adding phosphorus compounds or silicones also presents problems such as mold contamination and gas generation.
[0008] Furthermore, a liquid crystalline resin composition has been proposed that contains foamed inorganic particles in the liquid crystalline resin to improve flame retardancy, low gasity, surface appearance, and mechanical properties (Patent Document 5). However, the heat resistance of the liquid crystalline resin is insufficient, and the use of such foamed inorganic particles impairs thin-wall fluidity and mechanical strength, making it difficult to mold miniaturized and thin-walled parts. Even if molding is possible, the mechanical strength is insufficient, making the parts prone to breakage. Additionally, variations in the crushing rate of the foamed inorganic particles occur during the manufacturing of the resin composition, leading to large variations in product strength. In particular, for portable terminals such as smartphones and laptops, the parts must have sufficient strength to withstand impacts such as unintended drops because the terminals are frequently carried around. However, the resin composition has low mechanical strength, such as impact strength, making it difficult to apply to such parts. [Prior art documents] [Patent Documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 1-118567 [Patent Document 2] Japanese Patent Publication No. 2000-239503 [Patent Document 3] Japanese Patent Application Publication No. 7-109406 [Patent Document 4] Japanese Patent Publication No. 2000-154314 [Patent Document 5] Japanese Patent Publication No. 2004-168841 [Overview of the project] [Problems that the invention aims to solve]
[0010] The present invention has been made in view of the above circumstances, and aims to provide a fully aromatic liquid crystal polymer composition that has an excellent balance of flame retardancy, thin-wall fluidity, heat resistance, and mechanical strength. [Means for solving the problem]
[0011] In view of the above problems, the inventors of the present invention conducted diligent studies and found that by blending specific amounts of glass fibers and calcium carbonate with a fully aromatic liquid crystal polymer, a fully aromatic liquid crystal polymer composition with an excellent balance of flame retardancy, thin-wall fluidity, heat resistance, and mechanical strength can be obtained, thus completing the present invention.
[0012] In other words, the present invention encompasses the following preferred embodiments. [1] Contains 10 to 150 parts by mass of glass fiber and 0.1 to 7 parts by mass of calcium carbonate per 100 parts by mass of all aromatic liquid crystal polymer, wherein the all aromatic liquid crystal polymer is of formula (I) to (III) [ka] [In the formula, Ar1, Ar2, and Ar3 each independently represent a divalent aromatic group.] A fully aromatic liquid crystal polymer composition comprising repeating units represented by . [2] The repeating unit represented by equation (I) is Ar1 as shown in equations (1) and (2). [ka] A fully aromatic liquid crystal polymer composition according to [1], comprising one or more repeating units selected from the aromatic groups represented by . 〔3〕 The repeating units represented by formulas (II) to (III) are such that Ar2 and Ar3 are each independently of one another selected from the aromatic groups represented by formulas (1) to (4)
Formula
Formula
[0013] The wholly aromatic liquid crystal polymer composition of the present invention has an excellent balance of flame retardancy, thin-wall flowability, heat resistance and mechanical strength, and thus is suitably used in various applications such as electrical and electronic components of various communication equipment and electronic devices, for example, connectors, switches, relays, bobbins, capacitors, coils, motors, fans, test sockets, transformers, camera modules and antennas. [Mode for Carrying Out the Invention]
[0014] The wholly aromatic liquid crystal polymer used in the wholly aromatic liquid crystal polymer composition of the present invention is a wholly aromatic liquid crystal polymer that forms an anisotropic molten phase, which is referred to by those skilled in the art as a thermotropic liquid crystal polyester or a thermotropic liquid crystal polyester amide.
[0015] The property of the anisotropic molten phase of the wholly aromatic liquid crystal polymer can be confirmed by a usual polarization inspection method using an orthogonal polarizer, that is, by observing a sample placed on a hot stage under a nitrogen atmosphere.
[0016] As the wholly aromatic liquid crystal polymer used in the present invention, those having a crystal melting temperature of 290 to 400°C measured by a differential scanning calorimeter are preferred, those of 300 to 380°C are more preferred, those of 310 to 360°C are still more preferred, those of 315 to 355°C are particularly preferred, and those of 320 to 350°C are most preferred.
[0017] When the crystal melting temperature of the wholly aromatic liquid crystal polymer is lower than 290°C, the heat resistance to reflow soldering is poor, and when it exceeds 400°C, the moldability tends to decrease, which is not preferable.
[0018] In this specification and in the claims, "crystal melting temperature" refers to the peak temperature of the crystal melting temperature measured using a Differential Scanning Calorimeter (DSC) at a heating rate of 20°C / min. More specifically, after observing the endothermic peak temperature (Tm1) when measuring a sample of all aromatic liquid crystal polymer under heating conditions of 20°C / min from room temperature, the sample is held at a temperature 20 to 50°C higher than Tm1 for 10 minutes, then the sample is cooled to room temperature under cooling conditions of 20°C / min, and the endothermic peak is observed again under heating conditions of 20°C / min. The temperature at which the peak top is observed is defined as the crystal melting temperature (Tm) of the all aromatic liquid crystal polymer. For example, a DSC7020 manufactured by Hitachi High-Tech Science Corporation can be used as the measuring instrument.
[0019] The polymerizable monomers that constitute the constituent units of the all-aromatic liquid crystal polymer in the present invention include aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, and aromatic diols, while other components include, for example, aromatic aminocarboxylic acids, aromatic hydroxyamines, and aromatic diamines. The all-aromatic liquid crystal polymer in the present invention does not contain aliphatic polymerizable monomers and is composed only of aromatic polymerizable monomers. This makes it possible to ensure a good balance of each property, such as mechanical strength, heat resistance, fluidity, and flame retardancy.
[0020] Specific examples of aromatic hydroxycarboxylic acids include 4-hydroxybenzoic acid, 3-hydroxybenzoic acid, 2-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 5-hydroxy-2-naphthoic acid, 7-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid and their alkyl, alkoxy, or halogen-substituted derivatives, as well as ester-forming derivatives such as their acylids, ester derivatives, and acid halides. Among these, from the viewpoint of easily adjusting the heat resistance, mechanical strength, and melting point of the resulting all-aromatic liquid crystal polymer, it is preferable to include one or more selected from 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, more preferably to include 4-hydroxybenzoic acid, and even more preferably to include both 4-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid.
[0021] Specific examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, 3,4'-dicarboxybiphenyl, and 4,4"-dicarboxyterphenyl, their alkyl, alkoxy, or halogen-substituted derivatives, and their ester derivatives and ester-forming derivatives such as acid halides. Among these, from the viewpoint of effectively improving the heat resistance of the resulting all-aromatic liquid crystal polymer, it is preferable to include one or more selected from the group consisting of terephthalic acid, isophthalic acid, and 2,6-naphthalenedicarboxylic acid, and more preferably to include one or more selected from terephthalic acid and 2,6-naphthalenedicarboxylic acid.
[0022] Specific examples of aromatic diols include hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, and 2,2'-dihydroxybinaphthyl, their alkyl, alkoxy, or halogen-substituted derivatives, and their acylated derivatives, which are ester-forming derivatives. Among these, from the viewpoint of excellent reactivity during polymerization, those containing one or more selected from the group consisting of hydroquinone, resorcinol, 4,4'-dihydroxybiphenyl, and 2,6-dihydroxynaphthalene are preferred, and those containing one or more selected from hydroquinone and 4,4'-dihydroxybiphenyl are more preferred.
[0023] Specific examples of aromatic aminocarboxylic acids include 4-aminobenzoic acid, 3-aminobenzoic acid, 6-amino-2-naphthoic acid, alkyl, alkoxy, or halogen-substituted derivatives thereof, and ester-forming derivatives such as acylated, ester derivatives, and acid halides thereof.
[0024] Specific examples of aromatic hydroxyamines include 4-aminophenol, N-methyl-4-aminophenol, 3-aminophenol, 3-methyl-4-aminophenol, 4-amino-1-naphthol, 4-amino-4'-hydroxybiphenyl, 4-amino-4'-hydroxybiphenyl ether, 4-amino-4'-hydroxybiphenylmethane, 4-amino-4'-hydroxybiphenyl sulfide, and 2,2'-diaminobinaphthyl, their alkyl, alkoxy, or halogen-substituted derivatives, and their acylated derivatives, etc. Among these, those containing 4-aminophenol are preferred from the viewpoint of easily balancing the heat resistance and mechanical strength of the resulting all-aromatic liquid crystal polymer.
[0025] Specific examples of aromatic diamines include 1,4-phenylenediamine, 1,3-phenylenediamine, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, their alkyl, alkoxy, or halogen-substituted derivatives, and amide-forming derivatives such as their acylated derivatives.
[0026] The polymerizable monomers that form the constituent units of the total aromatic liquid crystal polymer in the present invention may include, to the extent that the objectives of the present invention are not impaired, other copolymerizing components such as dihydroxyterephthalic acid, 4-hydroxyisophthalic acid, 5-hydroxyisophthalic acid, trimellitic acid, 1,3,5-benzenetricarboxylic acid, pyromellitic acid, or alkyl, alkoxy, or halogen-substituted derivatives thereof, as well as ester-forming derivatives thereof such as acylated derivatives, ester derivatives, and acid halides. Preferably, the amount of these polymerizable monomers used is 10 mol% or less relative to the total constituent units of the total aromatic liquid crystal polymer.
[0027] In the present invention, the all-aromatic liquid crystal polymer may contain thioester bonds, to the extent that it does not impair the objectives of the present invention. Examples of polymerizable monomers that provide such bonds include mercaptoaromatic carboxylic acids, aromatic dithiols, and hydroxyaromatic thiols. The content of these polymerizable monomers is preferably 10 mol% or less relative to the total constituent units of the all-aromatic liquid crystal polymer.
[0028] Polymers formed by combining these repeating units may or may not form an anisotropic molten phase, depending on the monomer composition, composition ratio, and sequence distribution of each repeating unit within the polymer. However, the all-aromatic liquid crystal polymers used in this invention are limited to those that form an anisotropic molten phase.
[0029] Specific examples of combinations of polymerizable monomers that form the constituent units of the all-aromatic liquid crystal polymer used in the present invention include, for example, the following. 1) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl, 2) 4-Hydroxybenzoic acid / terephthalic acid / isophthalic acid / 4,4'-dihydroxybiphenyl, 3) 4-Hydroxybenzoic acid / terephthalic acid / isophthalic acid / 4,4'-dihydroxybiphenyl / hydroquinone, 4) 4-Hydroxybenzoic acid / terephthalic acid / hydroquinone, 5) 6-Hydroxy-2-Naphthoic Acid / Terephthalic Acid / Hydroquinone, 6) 4-Hydroxybenzoic acid / 6-Hydroxy-2-Naphthoic acid / Terephthalic acid / 4,4'-Dihydroxybiphenyl, 7) 6-hydroxy-2-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl, 8) 4-Hydroxybenzoic acid / 6-Hydroxy-2-Naphthoic acid / Terephthalic acid / Hydroquinone, 9) 4-Hydroxybenzoic acid / 6-Hydroxy-2-Naphthoic acid / Terephthalic acid / Hydroquinone / 4,4'-Dihydroxybiphenyl, 10) 4-Hydroxybenzoic acid / 2,6-Naphthalenedicarboxylic acid / 4,4'-Dihydroxybiphenyl, 11) 4-Hydroxybenzoic acid / terephthalic acid / 2,6-naphthalenedicarboxylic acid / hydroquinone, 12) 4-Hydroxybenzoic acid / 2,6-Naphthalenedicarboxylic acid / Hydroquinone, 13) 4-Hydroxybenzoic acid / 6-Hydroxy-2-naphthoic acid / 2,6-naphthalenedicarboxylic acid / hydroquinone, 14) 4-Hydroxybenzoic acid / Terephthalic acid / 2,6-Naphthalenedicarboxylic acid / Hydroquinone / 4,4'-Dihydroxybiphenyl, 15) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / 4-aminophenol, 16) 4-Hydroxybenzoic acid / terephthalic acid / 2,6-naphthalenedicarboxylic acid / 4,4'-dihydroxybiphenyl, 17) 6-Hydroxy-2-Naphthoic Acid / Terephthalic Acid / Hydroquinone / 4,4'-Dihydroxybiphenyl.
[0030] Among these, all aromatic liquid crystal polymers consisting of structural units derived from the polymerizable monomers 1), 2), 6), 8), 9), 13), and 17) are preferred, all aromatic liquid crystal polymers consisting of structural units derived from the polymerizable monomers 8), 9), 13), and 17) are more preferred, and all aromatic liquid crystal polymers consisting of structural units derived from the polymerizable monomers 9) and 13) are even more preferred.
[0031] The all-aromatic liquid crystal polymer used in the all-aromatic liquid crystal polymer composition of the present invention is excellent in terms of heat resistance and mechanical properties, as shown in formulas (I) to (III). [ka] [In the formula, Ar1, Ar2, and Ar3 each independently represent a divalent aromatic group.] Includes a repeating unit represented by .
[0032] Here, the repeating unit represented by formula (I) may be multiple types of repeating units, each containing a different Ar1; the repeating unit represented by formula (II) may be multiple types of repeating units, each containing a different Ar2; and the repeating unit represented by formula (III) may be multiple types of repeating units, each containing a different Ar3. That is, the repeating unit represented by formula (I) may be multiple repeating units, such as a repeating unit of one type of Ar1 and a repeating unit of another type of Ar1; similarly, the repeating unit represented by formula (II) may be multiple repeating units, such as a repeating unit of one type of Ar2 and a repeating unit of another type of Ar2; and the repeating unit represented by formula (III) may be multiple repeating units, such as a repeating unit of one type of Ar3 and a repeating unit of another type of Ar3. Furthermore, "aromatic group" refers to an aromatic group that is a 6-membered monoring (including biphenyl) or a fused ring with 2 rings.
[0033] In terms of excellent fluidity and mechanical properties, the composition ratio (mol%) of the repeating unit represented by formula (I) is preferably 30 to 80 mol%, and more preferably 40 to 70 mol%. The repeating units represented by formulas (II) and (III) are preferably 10 to 35 mol%, and more preferably 15 to 30 mol%. It is preferable that the repeating units represented by formulas (II) and (III) are substantially equimolar.
[0034] In the all-aromatic liquid crystal polymer containing repeating units represented by formulas (I) to (III), it is preferable that the repeating unit represented by formula (I) is one or more repeating units in which Ar1 is selected from the aromatic groups represented by the following formulas (1) to (2), in terms of ease of adjusting heat resistance, mechanical strength, and melting point. Among these, it is more preferable that the repeating unit contains the aromatic group represented by formula (1), and even more preferable that it contains both the aromatic groups represented by formulas (1) and (2). Furthermore, when both the aromatic groups represented by formulas (1) and (2) are contained, it is particularly preferable that the composition ratio (mol%) of formula (1) ≥ formula (2). [ka]
[0035] In the all-aromatic liquid crystal polymer containing repeating units represented by formulas (I) to (III), it is more preferable that the repeating units represented by formulas (II) to (III) are such that Ar2 and Ar3 are each independently selected from the aromatic groups represented by the following formulas (1) to (4), in terms of excellent fluidity and heat resistance. It is particularly preferable that the repeating unit represented by formula (II) is a repeating unit in which Ar2 is an aromatic group represented by formula (1) and / or formula (4), and the repeating unit represented by formula (III) is a repeating unit in which Ar3 is an aromatic group represented by one or more selected from the group consisting of formulas (1), (2), and (3). [ka]
[0036] The all-aromatic liquid crystal polymer containing repeating units represented by formulas (I) to (III) is more preferably an all-aromatic liquid crystal polyester consisting of repeating units represented by formulas (I) to (III) in that it can maintain a low water absorption rate.
[0037] The method for producing the all-aromatic liquid crystal polymer used in the present invention will be described below.
[0038] There are no particular limitations on the method for producing the all-aromatic liquid crystal polymer used in the present invention. The all-aromatic liquid crystal polymer can be obtained by subjecting a polymerizable monomer to a known polycondensation method that forms ester bonds or amide bonds, such as the melt acidolysis method or slurry polymerization method.
[0039] The molten acidolysis method is a preferred method for producing the all-aromatic liquid crystal polymer used in the all-aromatic liquid crystal polymer composition of the present invention. In this method, polymerizable monomers are first heated to form a molten solution of reactants, and then a polycondensation reaction is carried out to obtain a molten polymer. Vacuum may be applied to facilitate the removal of volatile by-products (e.g., acetic acid, water, etc.) produced in the final stage of condensation.
[0040] Slurry polymerization is a method of reacting polymerizable monomers in the presence of a heat exchange fluid, and the solid product is obtained suspended in the heat exchange medium.
[0041] In both the molten acidolysis method and the slurry polymerization method, the polymerizable monomers used in the production of all-aromatic liquid crystal polymers can also be used in the reaction at room temperature as modified forms with acylated hydroxyl and / or amino groups, i.e., lower acylated compounds.
[0042] The lower acyl group is preferably one having 2 to 5 carbon atoms, and more preferably one having 2 or 3 carbon atoms. In a preferred embodiment of the present invention, the acetylated product of the polymerizable monomer is subjected to the reaction.
[0043] The lower acylated polymers of polymerizable monomers may be synthesized beforehand by acylation, or they may be generated in the reaction system by adding an acylation agent such as acetic anhydride to the polymerizable monomer during the production of the all-aromatic liquid crystal polymer.
[0044] In either the molten acidolysis method or the slurry polymerization method, the polycondensation reaction is preferably carried out at a temperature of 150 to 400°C, preferably 250 to 370°C, under atmospheric pressure and / or reduced pressure, and a catalyst may be used if necessary.
[0045] Specific examples of catalysts include organotin compounds such as dialkyltin oxides (e.g., dibutyltin oxide) and diarylinoxides; titanium dioxide; antimony trioxide; organotitanium compounds such as alkoxytitanium silicates and titanium alkoxides; alkali and alkaline earth metal salts of carboxylic acids (e.g., sodium acetate, potassium acetate); and gaseous acid catalysts such as Lewis acids (e.g., boron trifluoride) and hydrogen halides (e.g., hydrogen chloride).
[0046] When a catalyst is used, the amount of the catalyst is preferably 1 to 1000 ppm, more preferably 2 to 100 ppm, relative to the total amount of polymerizable monomers.
[0047] The all-aromatic liquid crystal polymers obtained by such polycondensation reactions are typically removed from the polymerization reactor in a molten state, processed into pellets, flakes, or powder, and then subjected to melt-kneading with other components.
[0048] Pelletized, flake, or powdered all-aromatic liquid crystal polymers may be heat-treated in a substantially solid state under reduced pressure, under vacuum, or in an atmosphere of an inert gas such as nitrogen or helium, in order to increase their molecular weight and improve their heat resistance.
[0049] The heat treatment temperature is not particularly limited as long as the all-aromatic liquid crystal polymer does not melt, but is preferably 260 to 350°C, more preferably 280 to 320°C.
[0050] The melt viscosity of the all-aromatic liquid crystal polymer used in this invention (measured with a capillary rheometer, crystal melting temperature + 10 to 30°C, 1000 s) -1 The pressure is preferably 1 to 200 Pa·s, more preferably 3 to 100 Pa·s, even more preferably 4 to 80 Pa·s, and particularly preferably 5 to 40 Pa·s.
[0051] When the melt viscosity is less than 1 Pa·s, smudging and stringing tend to occur during injection molding, and when it exceeds 200 Pa·s, fluidity tends to decrease.
[0052] Examples of glass fibers used in the all-aromatic liquid crystal polymer composition of the present invention include long-fiber chopped glass fibers, short-fiber milled glass fibers, and others manufactured by various methods. Two or more of these can also be used in combination.
[0053] Examples of glass fibers used in the present invention include E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S-glass, and mixtures thereof. Among these, E-glass is preferred because it has excellent strength and is readily available.
[0054] The glass fibers used in this invention may be treated with a coupling agent such as a silane-based coupling agent or a titanium-based coupling agent, if necessary.
[0055] The glass fibers used in the present invention may be coated with a thermoplastic resin such as urethane resin, acrylic resin, or ethylene / vinyl acetate copolymer, or a thermosetting resin such as epoxy resin, or treated with a consolidating agent.
[0056] The number-average fiber diameter of the glass fibers used in the present invention is preferably 3 to 20 μm, more preferably 5 to 16 μm, and even more preferably 7 to 13 μm. The number-average fiber diameter of the glass fibers in the resulting all-aromatic liquid crystal polymer composition remains substantially unchanged even after melt kneading.
[0057] The raw material glass fibers used preferably have a cut fiber length of 10 mm or less. If the glass fibers are long-fiber chopped glass fibers, 1.5 to 6 mm is more preferable, and 2 to 4 mm is even more preferable. If the glass fibers are short-fiber milled glass fibers, 10 μm to 200 μm is more preferable, and 20 to 150 μm is even more preferable. From the viewpoint of availability and ease of handling, it is preferable to use long-fiber chopped glass fibers. The number-average fiber length of the glass fibers in the resulting all-aromatic liquid crystal polymer composition is preferably 10 to 600 μm, more preferably 30 to 500 μm, and even more preferably 50 to 450 μm. The glass fibers usually break or shatter during compounding and kneading with the all-aromatic liquid crystal polymer, etc., to obtain the number-average fiber length in the all-aromatic liquid crystal polymer composition. To obtain an all-aromatic liquid crystal polymer composition containing glass fibers of a desired fiber length, the melt-kneading conditions can be set and adjusted according to the cut fiber length of the glass fibers used.
[0058] The number-average fiber diameter and fiber length of glass fibers in an all-aromatic liquid crystal polymer composition can be measured by observation with a microscope. First, 1.0 g of the all-aromatic liquid crystal polymer composition is placed in a crucible and treated in an electric furnace at 500-600°C for 5 hours to ash it. The residue is dispersed in methanol and spread onto a glass slide to prepare the sample. Next, the length in the longitudinal direction is read as the fiber length and the length in the direction perpendicular to the longitudinal direction as the fiber diameter in the projected image of the glass fibers in the field of view of the microscope, and the arithmetic mean is calculated. The denominator for the mean value should be 200 or more.
[0059] In the all-aromatic liquid crystal polymer composition of the present invention, the glass fiber content is 10 to 150 parts by mass per 100 parts by mass of the all-aromatic liquid crystal polymer, preferably 12 to 120 parts by mass, more preferably 15 to 100 parts by mass, and even more preferably 20 to 80 parts by mass. If the glass fiber content is less than 10 parts by mass, the strength improvement effect due to the use of glass fibers tends not to be obtained, and if it exceeds 150 parts by mass, the fluidity tends to decrease.
[0060] Examples of calcium carbonate used in the all-aromatic liquid crystal polymer composition of the present invention include heavy calcium carbonate and precipitated calcium carbonate (light calcium carbonate, colloidal calcium carbonate). Among these, heavy calcium carbonate is preferred due to its excellent mechanical strength and fluidity.
[0061] The calcium carbonate used in this invention may be in powder form, for example, fine powder, granules, or whisker form, and its particle shape is not particularly limited. The average particle diameter is preferably 0.01 to 30 μm, more preferably 0.1 to 20 μm, even more preferably 1 to 15 μm, particularly preferably 2 to 12 μm, and most preferably 5.1 to 11 μm, in terms of excellent mechanical strength, thin-wall fluidity, and flame retardancy. The average particle diameter can be measured and calculated, for example, by measuring the particle diameter using a scanning electron microscope.
[0062] The calcium carbonate used in this invention may be surface-treated with phosphoric acid, fatty acids, fatty acid salts, fatty acid esters, polyacrylic acid, resin acids, various coupling agents, etc. However, due to the generation of volatile substances during molding caused by the surface treatment agent and the high cost of surface-treated calcium carbonate, untreated calcium carbonate is more preferably used.
[0063] In the all-aromatic liquid crystal polymer composition of the present invention, the calcium carbonate content is 0.1 to 7 parts by mass per 100 parts by mass of the all-aromatic liquid crystal polymer, preferably 0.15 to 6 parts by mass, more preferably 0.2 to 5 parts by mass, even more preferably 0.25 to 4 parts by mass, particularly preferably 0.3 to 3 parts by mass, and most preferably 0.35 to 2 parts by mass. If the calcium carbonate content is less than 0.1 parts by mass, the effect of improving flammability by using calcium carbonate tends not to be obtained, and if it exceeds 7 parts by mass, the mechanical properties and fluidity tend to decrease.
[0064] Furthermore, the all-aromatic liquid crystal polymer composition of the present invention may contain, in addition to the glass fibers and calcium carbonate described above, other fibrous, plate-like, or granular inorganic or organic fillers, to the extent that it does not impair the objectives of the present invention.
[0065] Other fibrous fillers used in the present invention include, for example, silica-alumina fibers, alumina fibers, carbon fibers, aramid fibers, polyarylate fibers, polybenzimidazole fibers, potassium titanate whiskers, aluminum borate whiskers, needle-shaped titanium oxide, calcium silicate such as wollastonite, xonotlite, calcium titanate, aluminum borate, basalt fibers, and tetrapod-type zinc oxide, which can be used individually or in combination of two or more.
[0066] Other plate-shaped fillers used in the present invention include, for example, talc, mica, kaolin, clay, graphite, vermiculite, calcium silicate, aluminum silicate, feldspar powder, acid clay, pyrophyllite clay, sericite, sillimanite, bentonite, glass flakes, slate powder, silicates such as silane, white pigment, carbonates such as barium carbonate, magnesium carbonate, dolomite, barite powder, precipitated calcium sulfate, calcined gypsum, sulfates such as barium sulfate, hydroxides such as hydrated alumina, alumina, antimony oxide, magnesia, titanium oxide, zinc oxide, silica, silica sand, white carbon, oxides such as diatomaceous earth, sulfides such as molybdenum disulfide, and plate-shaped wollastonite. These can be used individually or in combination of two or more.
[0067] Other granular fillers used in the present invention include, for example, silica, alumina, titanium oxide, glass beads, barium sulfate, boron nitride, silicon carbide, and resin beads, which can be used individually or in combination of two or more. Here, it is preferable not to include foamed inorganic particles because they reduce mechanical strength and, due to the low strength of the foamed inorganic particles themselves, cause crushing during the manufacture of the resin composition, leading to large variations in product strength. Examples of foamed inorganic particles include shirasu balloons, glass balloons, fly ash balloons, etc.
[0068] The content of these other fibrous, plate-like, or granular inorganic or organic fillers is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, per 100 parts by mass of the total aromatic liquid crystal polymer. If the content of these other fibrous, plate-like, or granular inorganic or organic fillers exceeds 50 parts by mass, the fluidity tends to decrease.
[0069] Furthermore, the all-aromatic liquid crystal polymer composition of the present invention may contain other additives, as long as they do not impair the effects of the present invention.
[0070] Other additives used in the present invention include, for example, lubricants such as higher fatty acids, higher fatty acid esters, higher fatty acid amides, and higher fatty acid metal salts (where higher fatty acids refer to those with 10 to 25 carbon atoms, for example); mold release improvers such as polysiloxanes and fluororesins; colorants such as dyes, pigments, and carbon black; flame retardants, antistatic agents, surfactants, antioxidants such as phosphorus-based antioxidants, phenol-based antioxidants, and sulfur-based antioxidants; weathering agents, heat stabilizers, and neutralizing agents. These additives may be used individually or in combination of two or more.
[0071] The content of these other additives is preferably 10 parts by mass or less, more preferably 0.01 to 5 parts by mass, per 100 parts by mass of the total aromatic liquid crystal polymer. If the content of these other additives exceeds 10 parts by mass, the thermal stability tends to deteriorate.
[0072] In the case of substances having an external lubricating effect, such as higher fatty acids, higher fatty acid esters, higher fatty acid metal salts, and fluorocarbon-based surfactants, these may be attached to the surface of the pellets of the all-aromatic liquid crystal polymer composition in advance when molding the all-aromatic liquid crystal polymer composition.
[0073] Furthermore, the all-aromatic liquid crystal polymer composition of the present invention may contain other resin components, to the extent that it does not impair the objectives of the present invention. Examples of other resin components include thermoplastic resins such as polyamide, polyester, polyacetal, polyphenylene ether and its modified products, polysulfone, polyethersulfone, polyetherimide, polyamideimide, and elastomer, as well as thermosetting resins such as phenolic resin, epoxy resin, and polyimide resin.
[0074] Other resin components may be included individually or in combination of two or more. The content of other resin components is not particularly limited and can be determined as appropriate depending on the application and purpose of the all-aromatic liquid crystal polymer composition. Typically, the total content of other resins is preferably 100 parts by mass or less, and particularly 50 parts by mass or less, per 100 parts by mass of the all-aromatic liquid crystal polymer.
[0075] A fully aromatic liquid crystal polymer composition can be obtained by blending a fully aromatic liquid crystal polymer, glass fibers, and calcium carbonate with other inorganic and / or organic fillers, other additives, and other resin components in a predetermined composition, and then melt-kneading them using a Banbury mixer, kneader, single-screw or twin-screw extruder, etc.
[0076] The all-aromatic liquid crystal polymer composition of the present invention, obtained in this manner, is molded or processed by known molding methods using an injection molding machine, an extruder, or the like.
[0077] The all-aromatic liquid crystal polymer composition of the present invention preferably exhibits a tensile strength of 80 MPa or higher, more preferably 90 MPa or higher, even more preferably 100 MPa or higher, and particularly preferably 110 MPa or higher, in a tensile test conducted in accordance with ASTM D638 using an ASTM No. 4 dumbbell specimen with a thickness of 3.2 mm. If the tensile strength is less than 80 MPa, the composition tends to be prone to breakage when used as a small, thin-walled part. The upper limit of the tensile strength is not particularly limited, but for example, it is 280 MPa.
[0078] The all-aromatic liquid crystal polymer composition of the present invention preferably has a tensile modulus of 10 GPa or higher, more preferably 11 GPa or higher, even more preferably 12 GPa or higher, and particularly preferably 13 GPa or higher, in a tensile test conducted in accordance with ASTM D638 using an ASTM No. 4 dumbbell test specimen with a thickness of 3.2 mm. If the tensile modulus is less than 10 GPa, it tends to be prone to breakage when used as a small, thin-walled part. The upper limit of the tensile strength is not particularly limited, but for example, it is 25 GPa.
[0079] The all-aromatic liquid crystal polymer composition of the present invention preferably exhibits a tensile elongation at break of 0.5% or more, more preferably 1% or more, and even more preferably 1.5% or more, in a tensile test conducted in accordance with ASTM D638 using an ASTM No. 4 dumbbell specimen with a thickness of 3.2 mm. If the tensile elongation at break is less than 0.5%, the composition tends to be prone to breakage when used as a small, thin-walled part. The upper limit of the tensile elongation at break is not particularly limited, but is, for example, 10%.
[0080] The all-aromatic liquid crystal polymer composition of the present invention exhibits an Izod impact strength of preferably 40 J / m or more, more preferably 50 J / m or more, even more preferably 65 J / m or more, and particularly preferably 80 J / m or more, in an Izod impact test compliant with ASTM D256 using a notched strip-shaped test piece measuring 63.5 mm in length, 12.7 mm in width, and 3.2 mm in thickness. If the Izod impact strength is less than 40 J / m, the material tends to be prone to breakage when used as a small, thin-walled part. The upper limit of the Izod impact strength is not particularly limited, but for example, it is 700 J / m.
[0081] The all-aromatic liquid crystal polymer composition of the present invention preferably has a load deflection temperature (DTUL, load 1.82 MPa) of 220°C or higher, more preferably 230°C or higher, and even more preferably 240°C or higher, when tested using a 3.2 mm thick, strip-shaped test piece (length 127 mm, width 12.7 mm) in accordance with ASTM D648. If the load deflection temperature is below 220°C, deformation is likely to occur during the reflow process, which is a processing step for electronic components, and the heat resistance tends to be poor. The upper limit of the above load deflection temperature is not particularly limited, but for example, it is 320°C.
[0082] The all-aromatic liquid crystal polymer composition of the present invention has a melt viscosity, measured at the crystal melting temperature + 10 to 30°C using a melt viscosity measuring device with a 1.0 mmφ × 10 mm capillary, preferably 3 to 70 Pa·s, more preferably 5 to 60 Pa·s, and even more preferably 10 to 50 Pa·s. If the melt viscosity is less than 3 Pa·s, problems such as dripping are likely to occur during injection molding, and if it exceeds 70 Pa·s, the fluidity tends to be insufficient.
[0083] The all-aromatic liquid crystal polymer composition of the present invention has a flow length of 0.1 mm thickness, as measured by the method described later, preferably 7 mm or more, more preferably 8 mm or more, even more preferably 9 mm or more, and particularly preferably 10 mm or more. If the flow length of 0.1 mm thickness is less than 7 mm, defects such as short shots tend to occur when forming small, thin-walled parts. The upper limit of the above flow length of 0.1 mm thickness is not particularly limited, but for example, it is 50 mm.
[0084] The all-aromatic liquid crystal polymer composition of the present invention preferably has a flammability rating of V-0 or V-1, more preferably V-0, in a 0.3 mm thickness test measured in accordance with the UL94 standard. If it is V-2 or less than V-2 (outside the standard range), it tends to have poor flame retardancy.
[0085] The all-aromatic liquid crystal polymer composition of the present invention has an excellent balance of flame retardancy, thin-wall flowability, heat resistance, and mechanical strength, and can be used as a molded product. It is particularly suitable for use in electronic components such as connectors, switches, relays, bobbins, capacitors, coils, motors, fans, test sockets, transformers, camera modules, and antennas. [Examples]
[0086] The present invention will be described below with reference to examples, but the present invention is not limited in any way to the following examples.
[0087] The crystal melting temperature, tensile strength, tensile modulus, tensile elongation at break, Izod impact strength, load deflection temperature, melt viscosity, 0.1 mm thickness flow length, and flame retardancy in the examples were tested and evaluated using the methods described below.
[0088] (1) Crystal melting temperature Using a differential scanning calorimeter (DSC7020, Hitachi High-Tech Science Co., Ltd.), the endothermic peak temperature (Tm1) observed when the temperature was raised from room temperature at a rate of 20°C / min was recorded. The sample was then held at a temperature 20-50°C higher than Tm1 for 10 minutes. Next, the sample was cooled to room temperature at a rate of 20°C / min, and the temperature at the peak of the exothermic peak observed at this time was defined as the crystallization temperature (Tc) of the all-aromatic liquid crystal polymer. Furthermore, the endothermic peak was observed again when the temperature was raised at a rate of 20°C / min, and the temperature at the peak of that peak was defined as the crystallization temperature (Tm) of the all-aromatic liquid crystal polymer.
[0089] (2) Tensile strength Using an injection molding machine (UH1000-110, manufactured by Nissei Plastic Industrial Co., Ltd.), dumbbell-shaped tensile test specimens (ASTM No. 4, 3.2 mm thick) were obtained by injection molding at a cylinder temperature of +10 to 30°C above the crystal melting temperature and a mold temperature of 70°C. Tensile tests were performed using an Autograph AG-X plus, manufactured by Shimadzu Corporation, in accordance with ASTM D638, with a span distance of 64.0 mm and a tensile speed of 5 mm / min.
[0090] (3) Tensile modulus The same test specimens used for tensile strength measurement were used, and the measurement was performed under the same conditions as for tensile strength measurement.
[0091] (4) Tensile elongation at fracture The same test specimens used for tensile strength measurement were used, and the measurement was performed under the same conditions as for tensile strength measurement.
[0092] (5) Izod impact strength Using an injection molding machine (UH1000-110, manufactured by Nissei Plastic Industrial Co., Ltd.), strip-shaped test specimens measuring 127 mm in length, 12.7 mm in width, and 3.2 mm in thickness were molded at a cylinder temperature of +10 to 30°C (crystal melting temperature) and a mold temperature of 70°C. These specimens were cut perpendicular to their length to obtain strip-shaped test specimens measuring 63.5 mm in length, 12.7 mm in width, and 3.2 mm in thickness. After notching, these specimens were measured in accordance with ASTM D256.
[0093] (6) Load-induced deflection temperature (DTUL) Using an injection molding machine (UH1000-110, manufactured by Nissei Plastic Industrial Co., Ltd.), strip-shaped test pieces measuring 127 mm in length, 12.7 mm in width, and 3.2 mm in thickness were molded at a cylinder temperature of +10 to 30°C above the crystal melting temperature and a mold temperature of 70°C. These were then measured in accordance with ASTM D648, with a load of 1.82 MPa and a heating rate of 2°C / min.
[0094] (7) Melt viscosity Using a melt viscosity measuring device (Capillograph 1D, manufactured by Toyo Seiki Co., Ltd.), a 1.0 mmφ × 10 mm capillary was measured at a shear rate of 1000 sec. -1The melt viscosity was measured under conditions of 350°C (320°C for Comparative Example 6, which will be described later, because the crystal melting temperature was lower).
[0095] (8) 0.1 mm thickness flow length A rectangular bar flow mold measuring 50 mm in length, 2.0 mm in width, and 0.1 mm in thickness was used for injection molding using an injection molding machine (NEX-15-1E, manufactured by Nissei Plastic Industrial Co., Ltd.) under the molding conditions shown in Table 1. The flow length was measured when the bar flow mold was filled with the material. For Comparative Example 6, described later, the cylinder temperature was set to 300-300-260°C because the crystal melting temperature was low.
[0096] [Table 1]
[0097] (9) Flame retardant (UL94) Test specimens measuring 170 mm in length, 12.7 mm in width, and 0.3 mm in thickness were prepared and left to stand for 48 hours at 23°C and 50% relative humidity before being evaluated in accordance with the UL94 standard.
[0098] The following describes the synthesis examples of the all-aromatic liquid crystal polymers used in the examples and comparative examples. The abbreviations for the compounds used in the synthesis examples are as follows.
[0099] [Monomers used in the synthesis of all-aromatic liquid crystal polymers (LCPs)] POB: 4-Hydroxybenzoic acid BON6: 6-hydroxy-2-naphthoic acid BP: 4,4'-Dihydroxybiphenyl HQ: Hydroquinone TPA: Terephthalic acid NDA: 2,6-Naphthalenedicarboxylic acid
[0100] Synthesis Example 1 (LCP1) In a reaction vessel equipped with a torque meter-equipped stirrer and distillation tube, POB, BON6, HQ, BP, and TPA were charged in the composition ratios shown in Table 2 to a total volume of 6.5 mol. Furthermore, acetic anhydride was charged at a ratio of 1.03 moles relative to the total amount of hydroxyl groups (moles) of monomers, and deacetic acid polymerization was carried out under the following conditions.
[0101] [Table 2]
[0102] The mixture was heated from room temperature to 150°C in 1 hour under a nitrogen gas atmosphere and held at that temperature for 30 minutes. Then, the mixture was heated to 350°C over 7 hours while distilling off the by-product acetic acid, and the pressure was reduced to 5 mmHg over 80 minutes. The polymerization reaction was terminated when the predetermined torque was reached, the contents of the reaction vessel were removed, and pellets of all aromatic liquid crystal polymer (LCP1) were obtained by grinding. The amount of acetic acid distilled during polymerization was approximately as per the theoretical value. The crystallization temperature (Tm) of the obtained pellets was 340°C.
[0103] Synthesis example 2 (LCP2) In a reaction vessel equipped with a torque meter-equipped stirrer and distillation tube, POB, BON6, HQ, and NDA were charged in the composition ratios shown in Table 3 to a total volume of 6.5 mol. Furthermore, acetic anhydride was charged at a ratio of 1.03 moles relative to the total amount of hydroxyl groups (moles) of monomers, and deacetic acid polymerization was carried out under the following conditions.
[0104] [Table 3]
[0105] The mixture was heated from room temperature to 150°C in 1 hour under a nitrogen gas atmosphere and held at that temperature for 30 minutes. Then, the mixture was heated to 350°C over 7 hours while distilling off the by-product acetic acid, and the pressure was reduced to 5 mmHg over 80 minutes. The polymerization reaction was terminated when the predetermined torque was reached, the contents of the reaction vessel were removed, and pellets of all aromatic liquid crystal polymer (LCP2) were obtained by grinding. The amount of acetic acid distilled during polymerization was approximately as per the theoretical value. The crystallization temperature (Tm) of the obtained pellets was 321°C.
[0106] Synthesis Example 3 (LCP3) In a reaction vessel equipped with a torque meter-equipped stirrer and distillation tube, POB and BON6 were charged in the composition ratios shown in Table 4 to a total volume of 6.5 mol. Furthermore, acetic anhydride was charged at a ratio of 1.03 moles relative to the total amount of hydroxyl groups (moles) of monomers, and deacetic acid polymerization was carried out under the following conditions.
[0107] [Table 4]
[0108] The mixture was heated from room temperature to 150°C in 1 hour under a nitrogen gas atmosphere and held at that temperature for 30 minutes. Then, the temperature was rapidly increased to 210°C while distilling off the by-product acetic acid and held at that temperature for 30 minutes. After that, the temperature was increased to 325°C over 5 hours, and then the pressure was reduced to 10 mmHg over 90 minutes. The polymerization reaction was terminated when the predetermined torque was reached, the contents of the reaction vessel were removed, and pellets of all aromatic liquid crystal polymer (LCP3) were obtained by grinding. The amount of acetic acid distilled during polymerization was approximately as per the theoretical value. The crystallization temperature (Tm) of the obtained pellets was 278°C.
[0109] The glass fibers and calcium carbonate used in the examples and comparative examples are shown below. Glass fiber: ECS03T-747H manufactured by Nippon Electric Glass Co., Ltd. (number average fiber diameter 10.5 μm, number average fiber length 3 mm) Calcium carbonate: Manufactured by Maruo Calcium Co., Ltd. Heavy calcium carbonate Super S (average particle size 6.3 μm)
[0110] Examples 1-5 and Comparative Examples 1-6 The synthesized LCP, glass fibers, and calcium carbonate were blended to the content (parts by mass) shown in Table 5. Melt-kneading was performed using a twin-screw extruder (TEX-30, manufactured by Japan Steel Works Ltd.) at a cylinder temperature of LCP crystal melting temperature + 10 to 30°C to obtain pellets of the liquid crystal polymer composition. Subsequently, tensile strength, tensile modulus, tensile elongation at break, Izod impact strength, load deflection temperature, melt viscosity, 0.1 mm thickness flow length, and flame retardancy were tested and evaluated using the method described above. The results are shown in Table 5.
[0111] As shown in Table 5, all of the all-aromatic liquid crystal polymer compositions in Examples 1 to 5 exhibited an excellent balance of thin-wall fluidity, heat resistance, and mechanical strength, as well as excellent flame retardancy.
[0112] In contrast, the all-aromatic liquid crystal polymer compositions of Comparative Examples 1 to 6 were inferior in any of the following areas: mechanical strength, heat resistance, fluidity, and flame retardancy, and did not adequately satisfy the balance of performance requirements. [Table 5]
Claims
1. The total aromatic liquid crystal polymer contains 10 to 150 parts by mass of glass fiber and 0.1 to 7 parts by mass of calcium carbonate per 100 parts by mass of total aromatic liquid crystal polymer, and the total aromatic liquid crystal polymer is of formula (I) to (III) 【Chemistry 1】 [In the formula, Ar 1 Ar 2 and Ar 3 Each of these independently represents a divalent aromatic group. A fully aromatic liquid crystal polymer composition comprising repeating units represented by .
2. The repeating unit represented by equation (I) is Ar 1 Equations (1) and (2) 【Chemistry 2】 The all-aromatic liquid crystal polymer composition according to claim 1, comprising one or more repeating units selected from aromatic groups represented by .
3. The repeating unit represented by equations (II) to (III) is Ar 2 and Ar 3 Each of these is independent of the others, and equations (1) to (4) 【Transformation 3】 The all-aromatic liquid crystal polymer composition according to claim 1, wherein each of the aromatic groups represented is selected from one or more repeating units.
4. All aromatic liquid crystal polymers are given by formulas (I) to (III) 【Chemistry 4】 [In the formula, Ar 1 , Ar 2 and Ar 3 each independently represent a divalent aromatic group] The all-aromatic liquid crystal polyester composition according to claim 1, comprising repeating units represented by .
5. The all-aromatic liquid crystal polymer composition according to claim 1, wherein the all-aromatic liquid crystal polymer has a crystal melting temperature of 290 to 400°C as measured by differential scanning calorimeter.
6. The all-aromatic liquid crystal polymer composition according to claim 1, wherein the Izod impact strength measured in accordance with ASTM D256 is 40 J / m or more.
7. The all-aromatic liquid crystal polymer composition according to claim 1, wherein the flammability of a 0.3 mm thickness, as measured in accordance with the UL94 standard, is V-0 or V-1.
8. The all-aromatic liquid crystal polymer composition according to claim 1, which does not contain foamed inorganic particles.
9. The all-aromatic liquid crystal polymer composition according to claim 1, wherein the calcium carbonate is heavy calcium carbonate.
10. The all-aromatic liquid crystal polymer composition according to claim 1, wherein the calcium carbonate has an average particle size of 0.01 to 30 μm.
11. A molded article comprising the all-aromatic liquid crystal polymer composition according to any one of claims 1 to 10.
12. The molded article according to claim 11, wherein the molded article is a component that constitutes one selected from the group consisting of connectors, switches, relays, bobbins, capacitors, coils, motors, fans, test sockets, transformers, camera modules, and antennas.
Citation Information
Patent Citations
Flame-retarding polyester composition
JP1989118567A
Flame-retardant liquid-crystal polyester composition
JP1995109406A
Flame-retardant resin composition and its molding product
JP2000154314A
Flame resistant liquid crystal resin composition
JP2000239503A
Liquid crystalline resin composition
JP2004168841A